(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
this article deals with the topic of the Mongol invasion and the subsequent struggle against their oppression.Sets the historical context for the Mongol conquests, highlighting their vast territorial expansion and the impact on the regions they conquered.Main Body:Describes the methods and strategies employed by the Mongol forces during their invasion, including their military prowess and use of terror tactics.Discusses the resistance efforts by various groups and regions against Mongol rule, highlighting both military and non-violent forms of resistance.Explores the socio-economic and cultural changes brought about by Mongol rule, including the establishment of trade networks and administrative systems.Examines the long-term consequences of the Mongol invasion on affected regions, including political, economic, and cultural shifts.Summarizes the key points discussed in the article, emphasizing the complex and multifaceted nature of the Mongol invasion and the subsequent struggle against their oppression.Considers the lasting legacy of the Mongol conquests and their impact on the development of the affected regions.The article provides a comprehensive overview of the Mongol invasion and the resistance efforts against their oppression, offering insights into the historical significance of this period.